The Mussa Theorem (and Other Results on IMF-Induced Moral Hazard) - Jeanne, Olivier (IMF Working Papers; Working Paper ;, 2004)
Using a simple model of international lending, we show that as long as the IMF lends at an actuarially fair interest rate and debtor governments maximize the welfare of their taxpayers, any changes in policy effort, capital flows, or borrowing costs in response to IMF crisis lending are efficient. Thus, under these assumptions, the IMF cannot cause moral hazard, as argued by Michael Mussa (1999, 2004). It follows that examining the effects of IMF lending on capital flows or borrowing costs is not a useful strategy to test for IMF-induced moral hazard. Instead, empirical research on moral hazard should focus on the assumptions of the Mussa theorem.